Consolidated Undrained Triaxial Compression Tests and Strength Criterion of Solidified Dredged Materials. (15th October 2018) - Ding, Jianwen; Feng, Xusong; Cao, Yupeng; Qian, Sen; Ji, Feng
Abstract : Consolidated undrained triaxial compression tests were performed to investigate the shear strength behavior of the solidified dredged materials (SDM). The variation law of deviator stress and excess pore water pressure with the increase of the applied confining pressure was investigated. It is found that the shear strength envelope is consisted of two lines, and there exists a transitional stress on the intersection point. The undrained shear strength develops slightly with the increase of applied normal stress in the preyield state. However, the undrained shear strength increases significantly in the postyield state, and the strength envelope is nearly a straight line with the extension through the origin. Based on the triaxial test data and the binary medium model, a strength criterion considering strength evolution mechanism is proposed and the relevant parameters of the strength criterion were discussed. Comparisons of the predicted results and experimental data demonstrate that the proposed strength criterion can properly describe the strength evolution rules of the SDM.